Analysis of Pediatric Procedural Dermatology at a Tertiary Care Referral Hospital in Eastern India - Sasmita Mishra; Alaka Sahoo; Anil Kumar Panda; Maitreyee Panda; Ajaya Kumar Jena (Wolters Kluwer Medknow Publications, 2024)
Background: Pediatric procedural dermatology is a broad and emerging aspect in the field of dermatology. Pediatric procedures require great expertise, skill, empathy, and confidence on the part of the treating physician. The challenging factors such as parental anxiety and doubts, the child's cooperation, and the risks versus benefits are further contributory. Objective: The objective of the study was to summarize the risks of intra- and postoperative complications/side effects during diagnostic and therapeutic procedure in the pediatric population. Materials and Methods: We conducted a retrospective study in our hospital. Patients were taken between ages 0 and 18 years who had attended the dermatology outpatient department from January 2019 to March 2022. Results: In a total of 527 outpatient department patients, 267 (50.66%) were males and 260 (49.33%) were females (male:female ratio 1.02:1). Out of diagnostic procedures, the most commonly performed procedures were punch biopsy (14.61%), followed by autologous serum skin test (11.81%) and slit-skin smear (1.90%). Out of 15 therapeutic procedures, intralesional steroids (21.34%) were the most frequently performed therapeutic procedure, followed by radiofrequency cauterization (16.51%), autologous skin therapy (6.98%), cryotherapy (8.76%), nail surgery (2.79%), chemical peeling (2.79%), comedone extraction (2.66%), chemical cauterization (2.54%), neodymium-doped yttrium aluminum garnet laser (2.16%), platelet-rich plasma therapy (1.39%), diode laser (1.27%), measles, mumps, and rubella vaccine injection (0.89%), fractional carbon dioxide laser (0.63%), suction blister epidermal grafting (0.63%), and platelet-rich fibrin therapy (0.25%). Conclusions: This study provided comprehensive data on the various dermatological procedures done for pediatric cases in a tertiary care teaching hospital. Both diagnostic and therapeutic procedures caused mild and transient side effects such as pain, edema, erythema, burning sensations, and irritation that did not affect the patient's lifestyle.